Creating An Environmentally Literacy Oriented E-Magazine on Household Waste Materials - Rahmi Rahmawati; Yulia Sukmawardani; Riri Aisyah (CV. Generasi Intelektual Digital (GEN ID), 2024)
This study aims to describe the appearance, analysis of the results of the validation test and the analysis of the results of the feasibility test of e-magazine environmental literacy oriented on the topic household waste. This study uses the DBR (Design Based Research) method through the preliminary stages (analysis and deepening of the material), design (initial product manufacture), and development (validation test and feasibility test product). The resulting product is an e-magazine environmental literacy oriented on household waste material entitled